MEREDUKSI PROKRASTINASI AKADEMIK MAHASISWA MELALUI TEKNIK TOKEN ECONOMY - Mujiyati, Mujiyati (JURNAL FOKUS KONSELING, 2015)
AbstractÂ The research is motivated by the indiscipline of students in attendance in class, working and collecting duties. That is the behavior of student academic procrastination. Therefore, efforts were made to solve the problem, one of them using a technique token economy. The purpose of this study was to determine the effect of the use of techniques token economy in reducing students academic procrastination. The research methodusing aquasi-experimentalanddata analysis techniquesusing the t test.The results showed that the use of techniques token economy proved to effectively reduce students academic procrastination.Â Keywords: Academic Procrastination, Reinforcement, Token Economy